Risk Management and Its Role in Business Success: Building Organizational Resilience Amid Global Uncertainty from a Prophetic Hadith Perspective - Maskur Maskur; Khuzaini Khuzaini (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
The research objective is to analyze risk management in business success, building organizational resilience amidst global uncertainty from the perspective of the Prophet's hadith. The method used is a combination of qualitative methods and literature research based on previous studies on the role of risk management. The results of this research show that risk management helps organizations understand their conditions, readiness, and capabilities in implementing organizational programs. Risk management is crucial and must be implemented because,, through formal, structured, and integrated risk management, an organization can adapt to its environment and provide appropriate policies to achieve program objectives. The management process has been exemplified in the Quran and applied directly by the Prophet Muhammad (SAW). While the Quran and the Prophet's hadith do not detail management practices explicitly, they provide principles that can be interpreted and applied. Management concepts such as planning, organizing, implementing, and monitoring, as well as leadership skills and competencies, are embedded within Islamic teachings found in the Quran and Hadith.